Backianadan Love: In the Life and Works of Mahatma Gandhi - Vazhappilly, Johnson (Journal of Dharma, 1992)
Joseph Francis, Backianadan Love: In the Life and Works of Mahatma Gandhi. Delhi: Sterling Publishers Private Limited, 1 991 .